2015
DOI: 10.1136/annrheumdis-2014-206323
|View full text |Cite
|
Sign up to set email alerts
|

Type 3 innate lymphoid cells producing IL-17 and IL-22 are expanded in the gut, in the peripheral blood, synovial fluid and bone marrow of patients with ankylosing spondylitis

Abstract: Type 3 innate lymphoid cells producing IL-17 and IL-22 are expanded in the gut, in the peripheral blood, synovial fluid and bone marrow of patients with ankylosing spondylitis Conclusions Gut-derived IL-17 + and IL-22 + ILC3 are expanded in the peripheral blood, SF and inflamed BM of patients with AS, suggesting the presence of an active homing axis between the gut and the inflamed sacroiliac joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
199
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 261 publications
(216 citation statements)
references
References 42 publications
12
199
0
5
Order By: Relevance
“…More recently, gut-derived IL-17 + IL-22 + ILCs have been found expanded in the peripheral blood, synovial fluid and inflamed bone marrow of patients with AS, suggesting the presence of an active homing axis between the gut and the inflamed sacroiliac joints [40]. In addiction, the authors reported a significant decrease in the percentage of intestinal and circulating IL-17 + IL-22 + ILC and in the expression of mucosal vascular addressin cell adhesion molecule 1 (MADCAM-1) related to the TNFi treatment efficacy [40].…”
Section: Enteropathic Spa: Insights On the Pathogenesismentioning
confidence: 99%
“…More recently, gut-derived IL-17 + IL-22 + ILCs have been found expanded in the peripheral blood, synovial fluid and inflamed bone marrow of patients with AS, suggesting the presence of an active homing axis between the gut and the inflamed sacroiliac joints [40]. In addiction, the authors reported a significant decrease in the percentage of intestinal and circulating IL-17 + IL-22 + ILC and in the expression of mucosal vascular addressin cell adhesion molecule 1 (MADCAM-1) related to the TNFi treatment efficacy [40].…”
Section: Enteropathic Spa: Insights On the Pathogenesismentioning
confidence: 99%
“…Cryptopatches are virtually absent in the ileum of normal subjects [37], suggesting that bacterial stimulation is necessary for them to develop in physiological conditions. Conversely, in the ileum of AS patients, increased expression of IL-7, mainly in the presence of PC, is associated with the presence of aggregates of LTi cells (CD3-c-kitþ/IL-7Rþ) that resemble murine cryptopatches [37] (Fig.…”
Section: Immune Alterations In the Gut Of Spa Patientsmentioning
confidence: 99%
“…2). In addition to their role in modulating the formation of cryptopatches, AS intestinal epithelial cells induce the differentiation of type III innate lymphoid cells (ILCs) [37]. ILCs are heterogeneous populations of lymphoid cells that do not display rearrangement of antigen receptors [38].…”
Section: Immune Alterations In the Gut Of Spa Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some immunological pathways may be actively involved in the transition of autoimmunity from the intestinal mucosa to the joint: Citrullinated immune complex formation deposition, shared antigenic targets (tTg) in the joint or intestinal (PAD), gut-joint epitope spreading, and migration of activated effector T cells from the gut to the joints, mimicking mucosal vaccine's effects on remote organs. Very recently, citrullination of the epithelial neutrophilactivating peptide 78/CXCL5 chemokine, resulted in activation of the monocyte-recruiting chemokine [52]. In fact, epithelial neutrophilactivating peptide 78/CXCL5 is expressed in intestinal inflammation, citrulline is preferentially synthesized in the gut epithelium and PADs reside in the local microbiome and the intestinal mucosa.…”
Section: Gut-joint Axismentioning
confidence: 99%